Thermal-exergetic behavior of a vertical double-tube heat exchanger with bubble injection. Issue 5 (3rd September 2019) - Pourhedayat, Samira; Sadighi Dizaji, Hamed; Jafarmadar, Samad
ABSTRACT: The use of air bubbles as a heat transfer improvement technique for heat exchangers has been proposed by some researchers. The vertical motion of tiny bubbles because of density difference with liquid provides extra vibration, eddies, turbulences, and consequently further heat transfer rate. The variety of affected parameters, such as injection method, air mass flow rate, bubbles size, number of perforations that forms bubbles, etc., has added to the complexity of this phenomena so that any change in the said parameters significantly influences the thermal-exergetic behavior of the heat exchanger. The quality and quantity of the impact of bubbles on the thermal performance of heat exchangers are different for any type of them. Moreover, each type of heat exchanger requires a specific injection method depending on the heat exchanger structure. In the present research, an injection way is proposed for vertical double-tube heat exchangers, and the effect of bubbles on thermal-exergetic characteristics is experimentally studied and discussed, which have not been performed before. Nondimensional exergy destruction, number of heat transfer units, and effectiveness are the main evaluated parameters in the present paper. Results showed a significant thermal improvement of the heat exchanger under the bubble injection.